Hubungan Lingkar Kepala Dengan Prestasi Belajar Pada Anak SD N 1 Tambongwetan Kalikotes - anna Uswatun (INVOLUSI: Jurnal Ilmu Kebidanan, 2019)
Brain growth is one of the things that changes, if nutritional intake is reduced, some parts of the brain development will be disrupted. The result of malnutrition will result in obstruction of the body and brain development, where head circumference is used as a parameter to determine it. In the growth parameters, there are several body parts that are measured including body weight, height, head circumference and chest circumference, if there is one that is less than normal it can affect learning achievement. The purpose of this study was to find out "the relationship between head circumference and learning achievement in SD N 1 Tambongwetan children". This study used an analytic survey method with a cross sectional design. The research population comprised all grade 1 and 2 students at SD N 1 Tambongwetan as many as 46 students. Sampling using total sampling. Data analysis using Kendall Tau. The results of data analysis showed ???? = 0.337 with a P value = 0.016; P value <0.05. The conclusion of the results of this study is that there is a relationship between head circumference and learning achievement in SD N 1 Tambongwetan children. Suggestion to parents should always pay attention to their children's nutritional intake because adequate nutrition can affect the growth of body size including head circumference.